Assessment of the molecular diversity of pelian (tor tambra ) in Sabah using mitochondrial and microsatellite DNA markers - Helena Biun (2023)
Tor tambra is a cyprinid riverine fish known as Pelian in local Sabahan, Malaysia Borneo, which known to have aquaculture and conservation worth. Applying conservation strategies and a sustainable management program necessitates a comprehensive understanding of genetic diversity and population structure. Eighteen wild Pelian populations were analyzed based on microsatellite markers and mtDNA D-loop. Pelian possesses microsatellite gene diversity and allelic richness of 0.40-0.68 and 2.63-6.10, respectively and mtDNA D-loop haplotype and nucleotide diversities of 0.000 to 0.911 and 0.001 to 0.021, respectively. Pairwise Fst values for microsatellite and Φst values for mtDNA D-loop were significant (P<0.05) between many population pairs. Microsatellites analyses of molecular variance, AMOVA analyses showed variances were found within populations (60.85% and 50.74% for grouping by watershed and Crocker Trusmadi Range, CTR, respectively) whereas mtDNA D-loop region revealed most variances were among groups (95.63% and 73.77% for grouping by watershed and CTR, respectively) with significantly high Φst and Fst values. Mantel tests supported weak patterns of differentiation as a result of isolation by distance. Analyses on genetic distance-based relationships (NJ, MP, UPGMA, Bayesian, haplotype network) and model-based clustering (BAPS, STRUCTURE) were consistent with partitioning the overall populations into two well differentiated cluster and further sub-structured according to watershed. Isolation by distance, river fragmentation and historical isolation by CTR significantly explain the genetic population structure. The genetic stock identification and delineation of the biological management units (MU) and conservation units (ESU) can used in identifying and prioritizing populations in need of management and conservation intervention. These data can also be used by the resource manager in decision-making and strategy-formulation process regarding Pelian stock enhancement programs. Information on the genetic variation can be used in the determination of base-line stocks for selective breeding program. However, prior to the adoption of management and conservation measures, there are still knowledge gaps from other disciplines that needs to be explored in order to support and complement the genetic results and to further enhance the management, conservation and breeding strategies formulations.